Risk factors for emergency presentation with lung and colorectal cancers: a systematic review - Una MacLeod; Elizabeth D Mitchell; Benjamin Pickwell-Smith (BMJ Open)
Objective To identify patient and practitioner factors that influence cancer diagnosis via emergency presentation (EP).Design Systematic review.Data sources MEDLINE, EMBASE, CINAHL, EBM Reviews, Science and Social Sciences Citation Indexes, Conference Proceedings Citation Index-Science and Conference Proceedings Citation Index-Social Science and Humanities. Searches were undertaken from 1996 to 2014. No language restrictions were applied.Study selection Studies of any design assessing factors associated with diagnosis of colorectal or lung cancer via EP, or describing an intervention to impact on EP, were included. Studies involving previously diagnosed cancer patients, assessing only referral pathway effectiveness, outcomes related to diagnosis or post-EP management were excluded. The population was individual or groups of adult patients or primary care practitioners. Two authors independently screened studies for inclusion.Results 22 studies with over 200 000 EPs were included, most providing strong evidence. Five were graded ‘insufficient’, primarily due to missing information rather than methodological weakness. Older patient age was associated with EP for lung and colorectal cancers (OR 1.11–11.03 and 1.19–5.85, respectively). Women were more at risk of EP for lung but not colorectal cancer. Higher deprivation increased the likelihood of lung cancer EP, but evidence for colorectal was less conclusive. Being unmarried (or divorced/widowed) increased the likelihood of EP for colorectal cancer, which was also associated with pain, obstruction and weight loss. Lack of a regular source of primary care, and lower primary care use were positively associated with EP. Only three studies considered practitioner factors, two involving diagnostic tests. No conclusive evidence was found.Conclusions Patient-related factors, such as age, gender and deprivation, increase the likelihood of cancer being diagnosed as the result of an EP, while cancer symptoms and patterns of healthcare utilisation are also relevant. Further work is needed to understand the context in which risk factors for EP exist and influence help-seeking.